Effect of surface machining on the corrosion behaviour of 316 austenitic stainless steel in simulated PWR water. (September 2017) - Wang, Siyang; Hu, Yujin; Fang, Kewei; Zhang, Wenqian; Wang, Xuelin
Highlights: The corrosion behaviour of 316 austenitic stainless steel with different surfaces in PWR primary water was investigated. The thickness and thickness uniformity of inner oxide film were affected by surface machining technique. Elemental distribution of the oxide film was influenced by the degree of surface cold working. The more heavily cold worked layer results in more aggravated chromium depletion and iron depletion beneath oxide film. Abstract: The corrosion behaviour of 316 austenitic stainless steel with different surface machining processes in simulated pressure water reactor primary environment was investigated. The oxide films related to three surface conditions were characterized by using SEM, TEM and XPS. The results showed that the machined surface conditions affected the thickness and elemental distribution of the oxide films composed of a double-layer structure. The more heavily cold worked layer results in less chromium enrichment in the inner film, and more nickel enrichment at the oxide/metal interface. Meanwhile, unduly chromium depletion beneath the oxide film was observed on the machined surfaces.